An Experimental Trial of an Infrared Sensor-Based Simple Pendulum Apparatus to Foster Senior High School Students’ Critical Thinking Skills on Simple Harmonic Motion - Nong Astriyana; Lutfia Maulidina (Journal of Advances in Physics Education, 2026)
Critical thinking is a fundamental 21st-century skill, yet its development in physics education remains challenging, especially in abstract topics such as Simple Harmonic Motion (SHM). Traditional pendulum experiments often rely on manual procedures, limiting students’ engagement in higher-order thinking. Objective: This study investigates the effectiveness of a low-cost infrared sensor-based simple pendulum apparatus in fostering senior high school students’ critical thinking skills on SHM. Methods: A pre-experimental one-group pretest–posttest design was implemented involving 97 eleventh-grade science students. The intervention consisted of guided-inquiry learning sessions using the custom-built apparatus integrating an infrared sensor and an Arduino microcontroller. Critical thinking skills were measured using a validated Likert-scale questionnaire encompassing four dimensions: Conceptual Understanding, Data Analysis & Interpretation, Reflection & Evaluation, and Collaboration & Interest. Descriptive statistics and normalized gain values were employed to assess improvement. Results: Findings revealed consistent improvement across all dimensions, with the highest gains observed in Collaboration & Interest (+2.07) and Conceptual Understanding (+2.01), followed by Data Analysis & Interpretation (+2.00) and Reflection & Evaluation (+1.79). Conclusion: The integration of the infrared sensor-based pendulum apparatus effectively enhanced students’ critical thinking skills. Automating data collection reduced cognitive load associated with procedural tasks, enabling students to focus on analysis, evaluation, and collaborative inquiry. This study concludes that the apparatus is a viable pedagogical innovation capable of transforming traditional physics laboratories into inquiry-oriented learning environments that support the development of essential higher-order thinking skills.